Analisis Prediksi Kebangkrutan dengan Metode Altman Z-Score dan Springate pada Perusahaan Subsektor Tekstil dan Garmen yang terdafar di Bursa Efek Indonesia - Soviyani, Evi; Cahyaningdyah, Permatasari; Prihadyatama, Ardila (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Financial instability in Indonesian companies can increase the risk of bankruptcy. A significant decline in textile and garment exports indicates signs of a financial crisis that threatens companies. This study focuses on analyzing the potential for bankruptcy using the Altman Z-Score and Springate methods while measuring accuracy by comparing the prediction results with the IDX special notation. The type of research used is descriptive quantitative. The sample was determined using purposive sampling techniques. The research results show that the Altman Z-Score method predicts that 3 companies are in a healthy condition and 5 companies are at risk of bankruptcy. Meanwhile, the Springate method predicts that 7 companies are at risk of bankruptcy and 1 company is in a healthy condition. The accuracy rate shows that the Springate method has a higher accuracy of 58.3% compared to the Altman Z-Score at 46%. The Springate method is more accurate and effective in predicting bankruptcy. The implications of this study indicate that bankruptcy prediction information can provide creditors and investors with an overview of a company's bankruptcy risk.